Sex differences in associations between spatial ability and corpus callosum morphology. Issue 8 (10th May 2018) - Kurth, Florian; Spencer, Debra; Hines, Melissa; Luders, Eileen
Abstract: Rotating mental representations of objects is accompanied by widespread bilateral brain activations. Thus, interhemispheric communication channels may play a relevant part when engaging in mental rotation tasks. Indeed, links between mental rotation and dimensions of the corpus callosum—the brain's main commissure system—have been reported. However, existing findings are sparse and inconsistent across studies. Here we set out to further characterize the nature of any such links, including their exact location across the corpus callosum. For this purpose, we applied an advanced image analysis approach assessing callosal thickness at 100 equidistant points in a sample of 38 healthy adults (19 men, 19 women), aged between 22 and 45 years. We detected a sex interaction, with significant structure–performance relationships in women, but not in men. Specifically, better mental rotation performance was linked to a thicker female corpus callosum within regions of the callosal splenium, posterior midbody, and anterior third. These findings may suggest sex differences in problem solving strategies where in women, more than in men, stronger interhemispheric connectivity—especially between occipitoparietal, frontal, and prefrontal regions—is associated with improved task performance. © 2018 Wiley Periodicals, Inc.